Insider Jesus : theological reflections on new Christian movements - Dyrness, William A. (Downers Grove : InterVarsity Press, 2016)
Amidst the variegated spread of global Christianity, followers of Jesus are showing up in unexpected places. Today we hear of culturally embedded insider movements, Jesus followers in the folds and creases of Islamic, Hindu, Buddhist, and other cultural fabrics. They elude our conventional theological categories and elicit wonder and debate. Are these authentic expressions of Christian faith? And if so, how should we understand them? William Dyrness brings a rare blend of cultural and theological engagement to his reflections on these insider movements. Could it be that our own understanding of what God is doing in the world is culturally shaped and needs recalibrating? How might the story of Israel and the early emergence of Jewish followers of Jesus provide helpful perspective on what we are seeing today? What is God already doing amidst a culture and people before the missionary arrives? And how might American Christians need to rethink the nature of religion? Within the present ferment and conversation, Dyrness's probings and reflections open up a theological space for exploring these questions anew.
The rise of contextualization -- How does God work in creation and culture?: a theological proposal -- Religion in the biblical narrative -- Case studies of insider movements today -- Religion and the mission of Christ -- Is God doing something new?
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050, 082, 650
Keywords: Insider movements; Missions -- Theory; Christianity and culture; Christianity and culture; Insider movements; Missions -- Theory; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books